The effect of Rabbit urine and Bokashi addition on the stem growth of Shallots (Allium ascalonicum L.) - Esna Dilli Novianto; Muh. Alwi Husen; Sugiyarto Sugiyarto (Journal of Natural Sciences and Mathematics Research, 2021)
Bokashi is a fermented rice straw. It is widely used as an organic fertilizer in Indonesia. It maintains the porosity of the soil, so the plant can grow perfectly. Rabbit urine on the other hand can be used as another nitrogen source. However, there is no report about the effect of both combination in shallots production (Allium ascalonicum L.), one of the main commodities in Magelang. For a better understanding on bokashi and rabbit urine, this experiment aims to study about its addition on the stem growth of shallots. Four dosages of rice straw bokashi were used. There are B0 (0kg/plot), B1 (3 kg/plot), B2 (4 kg/plot), and B3 (5kg/plot).  While the concentration of rabbit urine are P0 (0 mL/L), P1 (175 mL/L), and P2 (250 mL/L). The growth of the stem is measured every one week until it reached the full growth. This study showed that the addition of bokashi hinder the stem’s growth. It turned out that too many bokashi will raise the temperature of the soil and inhibit the plant’s growth.©2021 JNSMR UIN Walisongo. All rights reserved.